(untitled) (Journal of Economic Research & Business Administration, 2016)
Any economic union during the development goes through various stages of integration. Eurasian Economic Union has been created only a year ago, but it is clear how many changes in some areas are expected in the fu- ture. All countries have decided to create a single financial market of EAEU by 2025. EAEU countries (Kazakhstan, Kyrgyzstan, Russia, Belarus, Armenia) differ in the degree of economic development. So, if these five states want to create a single financial market they have to solve many problems and pre- pare conditions that take into account the interests of each side. Therefore, article analyzes the information about the economic development, potential of the securities market and legal circumstances of each country. Currently, the Union consists of five countries, but in the future this number may grow. So, they need a full analysis of financial market of each state. The article de- scribes stock markets of the EAEU and reviews laws that regulate the securities market. This analyzed features help to determine the benefits and obstacles of the creation of a single financial market, including the stock market.